Study on the influence of infragravity waves on inundation characteristics at Minami-Ashiyahama in Osaka Bay induced by the 2018 Typhoon Jebi. Issue 2 (2nd April 2020) - Hattori, Naohiro; Tajima, Yoshimitsu; Yamanaka, Yusuke; Kumagai, Kenzou
ABSTRACT: Typhoon Jebi struck Osaka Bay, Japan, on September 4, 2018. It recorded the highest storm surge level ever in the inner part of Osaka Bay and caused severe damage to many coastal areas. Minami-Ashiyahama, Hyogo Prefecture, suffered from severe inundation by overtopping waves induced by the typhoon. The inundation volume was estimated through numerical simulation and the results suggested that the wave overtopping rate is highly sensitive to the tide level and could have been 1.5 ~ 2 times larger with water level rise of 50 cm at 4.5 m wave height. A video taken at Minami-Ashiyahama captures overtopping waves entering the residential area. The analysis of the video suggests the pattern of overtopping changing before and after peak tide level, and indicates the influence of slowly varying water level fluctuations including infragravity waves on the inundation volume. Spectral analysis of observed data at tide gauge stations were then conducted. The results show long wave components developing just before peak tide level, and suggests the influence of long waves to coastal disasters. A numerical simulation also suggested that the bay-scale and harbor-scale resonance of long wave components could have influenced the inundation characteristics at Minami-Ashiyahama.